If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(-4x + 9) = 16 + -2x Reorder the terms: 12(9 + -4x) = 16 + -2x (9 * 12 + -4x * 12) = 16 + -2x (108 + -48x) = 16 + -2x Solving 108 + -48x = 16 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 108 + -48x + 2x = 16 + -2x + 2x Combine like terms: -48x + 2x = -46x 108 + -46x = 16 + -2x + 2x Combine like terms: -2x + 2x = 0 108 + -46x = 16 + 0 108 + -46x = 16 Add '-108' to each side of the equation. 108 + -108 + -46x = 16 + -108 Combine like terms: 108 + -108 = 0 0 + -46x = 16 + -108 -46x = 16 + -108 Combine like terms: 16 + -108 = -92 -46x = -92 Divide each side by '-46'. x = 2 Simplifying x = 2
| 119=n-66 | | 15x-20(4/15+5/15x)=-7 | | -(8y+2)-(-7y-8)=3 | | 5y^3*3y^5= | | z=3+j | | 6x+7(4-x)=23 | | 2(7v-3)=22 | | t+27=15 | | y=x^5-2x^3+x-3 | | 4(2u-3)=24 | | (x-2)(x^2-4x+3)=0 | | log(2x+6)144=2 | | 4x+8+3x-5=129 | | 6(4-x)+7y=23 | | x^3+2x+8=0 | | x-3(9+x)=-11 | | x-3(9+x)=-11 | | 2(2x+3)-4(2-3x)=6+x | | 14-2(3p+p)=6(4+p) | | 5(2x+8)=7x+20 | | 0.05x+0.04y=420 | | -7-2x=-19 | | -1(3z+4)=6z+-3(3z+2) | | 3(2x+4)-x=11 | | f(x)=3x^2+6x-7 | | 5c-4(9-c)= | | 5c+4c= | | 3(2x+5)-x=11 | | 5c+4n= | | [x-3]=12 | | z+30=16 | | 14+3n=8n-3(1n-4) |